Indicadores de sustentabilidade da carcinicultura em terras baixas, São Cristovão, Sergipe - Muhlert, Ana Carolina Souto (2014)
Since the emergence of the environmental consciousness as a result of increased pressure from environmentalists who fight against the overuse of natural resources, sustainable development has become a major challenge since the twentieth century. As a means to ensure sustainable development, Brazil has been developing environmental policies which have instruments such the environmental licensing. The shrimp farming is an activity which has polluting potential, therefore to be developed within the law it has to go through the licensing process. At São Cristóvão municipality, Sergipe State, shrimp farm has been developed mostly by smallholders in Permanent Preservation Areas. Due to the location of aquaculture estuarine ponds that have existed for about 200 years, those shrimp ponds do not have licensing and, if on the one hand, closing those ponds would be ideal under the environmental point of view, it would also be responsible for an enormous negative socioeconomic impact to the actors involved in this activity. Thus, this study aimed to evaluate sustainability in social, economic and ecological dimensions of marine shrimp farm in São Cristóvão, through the use of indicators based on the methodology Framework for Assessment Systems Natural Resources Management Incorporating Sustainability Indicators (MESMIS). At the study literature searches were performed in addition to query a database of the Study Group on Aquaculture and Sustainability (GEAS), which provided data about shrimp farmers and actors involved in the activity. 30 indicators were selected and it was observed that the economic dimension obtained the highest level of sustainability (86.04%), followed by social dimension (80.37%) and ecological dimension (67.78%), respectively. The general index found for the shrimp farms studied in São Cristóvão was 78.06%, confirming the hypothesis that the local marine shrimp farms are sustainable considering the economic, social and ecological dimensions. However, more studies are needed in order to deepen the knowledge about sustainability in the study area.